Ceramic tiles with controlled porosity and low thermal conductivity by using pore-forming agents - Novais, Rui M.
This work reports the influence of pore forming agents, their incorporation content and particle size distribution on the bi-layered ceramics porosity, mechanical resistance and thermal conductivity. The results demonstrate that the porosity level on the hi-layered ceramics bottom layer can be easily controlled by the porogen amount, while porogen particle size affects both the number and size distribution of the pores. Two different pore forming agents were evaluated, namely polypropylene (PP) and polymethyl methacrylate (PMMA). The nature of the pore forming agent, however, did not affect the hi-layered ceramics' properties. The incorporation of porosity into the hi-layered ceramics promotes thermal conductivity attenuation (up to 79%) in comparison with conventional porcelain stoneware ceramics, yet maintaining suitable mechanical strength. Thermal conductivity decrease is adjustable as a function of the volume and size of the generated pores, thus enabling materials to be tailored for the envisaged applications. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.